OPTIMALISASI SDM DAN INOVASI GREEN MARKET SEBAGAI STRATEGI PEMASARAN WISATA PADA SENTRA UMKM GROSIR BATIK JAWON: Indonesia - Ratna Agustina; Dwi Dewianawati; Silvya Nanda Putri; Moch. Nurrozikin Romadhon (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
knowledge of effective marketing strategies amidst intense business competition and evolving market demands, especially in the current digital era and society 5.0. This community service research through a tourism program employed qualitative methods with a case study approach. Data collection was conducted through brief interviews and documentation. This results indicate that human resource optimization and green marketing innovation mutually reinforce each other in creating a competitive advantage for the Jawon Batik Wholesale MSME center. For the program's sustainability, it is recommended that MSMEs continue to innovate products and actively collaborate with travel agents and local governments to strengthen promotions. These ongoing efforts will ensure the Jawon Batik production center remains relevant and competitive in an increasingly environmentally conscious market.